PENGARUH MODEL ROLE PLAYING TERHADAP KEMAMPUAN KOMUNIKASI PESERTA DIDIK DI SEKOLAH DASAR - Fathia Rahmah, Mutia; Nasution, Sahkholid (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Communication skills are also the skills of pronouncing articulation sounds or words to express, state thoughts, ideas, and feelings of learning Indonesian. The results of interviews at MIN 2 Southeast Aceh, students' communication skills vary, namely moderate, stuttering, and lacking. Lack of confidence in communicating, and teachers only use 1 learning model when teaching. The purpose of this study was to analyze how the influence of the role-playing learning model on the communication skills of class V students of MIN 2 Southeast Aceh. This study uses a quantitative research type with a posttest only control group design. Focus on the posttest only control group design. The research sample used was the experimental class, namely class VA using the role playing learning model and the control class, namely VB using the direct learning model. the results of the study and discussion can be concluded that there is an influence on students' communication skills between classes that are given treatment using the Role Playing learning model and classes that are given direct learning models in class V MIN 2 Southeast Aceh. Because the role-playing learning model assigns students to work together in groups in acting out a story so that it can improve students' communication skills. This is indicated by the sig.0.000 <0.05 value. The implication of this research is that the Role Playing learning model is able to provide an overview that this model can influence student communication, therefore it is hoped that the Role Playing learning model can be applied to other subjects. Keywords: Role Playing Model; Communication Skills